Cost of managing patients with venous leg ulcers. Issue 4 (7th May 2020) - Phillips, Ceri J.; Humphreys, Ioan; Thayer, Dan; Elmessary, Muhammad; Collins, Huw; Roberts, Chris; Naik, Gurudutt; Harding, Keith
Abstract: The aim of this study was to estimate costs associated with the management of patients with venous leg ulcers (VLUs) from the perspective of the UK National Health Service (NHS). The analysis was undertaken through the Secure Anonymised Information Linkage Databank which brings together and anonymously links a wide range of person‐based data from around 75% of general practitioner (GP) practices within Wales (population coverage ~2.5 million). The data covered an 11‐year period from 2007 to 2017. All patients linked to the relevant codes were tracked through primary care settings, recording the number of GP practice visits (number of days with an event recorded), and wound treatment utilisation (eg, dressings, bandages, etc.) Resources were valued in monetary terms (£ sterling) and the costs were determined from national published sources of unit costs. This is the first attempt to estimate the costs of managing of VLUs using routine data sources. The direct costs to the Welsh NHS are considerable and represent 1.2% of the annual budget. Nurse visits are the main cost driver with annual estimates of £67.8 million. At a UK level, these costs amount to £1.98 billion. Dressings and compression bandages are also major cost drivers with annual Welsh estimates of £828 790. The direct cost of managing patients with VLUs is £7706 per patient per annum, which translates to an annual cost of over £2 billion, when extrapolated to the UK population. The primary cost driver is the number of district nurse visits. Initiatives to reduce healing times through improving accuracy of initial diagnosis, and improved evidence‐based treatment pathways would result in major financial savings.